Ethics and the Economic Interpretation - Knight, Frank H. (Quarterly Journal of Economics, 1922)
Bearing on problem of scope and method, 454. — Both economics and ethics deal with value, 454. — Economics as a pure science has given too little attention to separation of constants from variables, 455. — Sense in which wants can be considered as data, 455. — Economic interpretation as a theory of conduct, 459. — Are human motives predominantly economic, 460. — Are they predominantly instinctive, 466. The adaptation theory, 469. — The pleasure theory, 469. — Economics as a study of the adaptation of means to ends, 472. — What becomes of ethics, 476. — Three kinds of treatment of conduct, 481.